Quality of bottled waters in Turkey - Pehlivan, Rustem (Journal of Nepal Geological Society, 2007)
In Turkey, 103 bottled waters (from natural springs and mineral waters) were sampled for testing their quality. The test revealed that in them some ions exceed the limits permitted by the World Health Organisation, European Community, and Turkish Standards. The appearance of Fe, Zn, As, and Al in the natural spring and mineral waters indicates their inorganic contamination. Such bottled waters can cause adverse effects on human health. If the information reported on the bottled water consumed in Turkey and other countries of the world is updated with current results of water chemistry analysis, consumer’s confidence in companies that produce them will increase.